Evaluation of Mechanical Properties of Soft Magnetic Materials for Axial Flux Permanent Magnet Synchronous Machines - Praunseis, Z.; Virtič, P. (Acta Technica Jaurinensis, 2013)
Accurate determination of soft magnetic material mechanical properties is important for operation of axial flux permanent magnet synchronous machines (AFPMSM). The aim of the paper is systematic experimental approach for determination of mechanical properties of high strenght low alloyed steels and mild carbon steel in the direction of steel rolling, steel plate thickness and width. These steels can be used as a rotor yoke in AFPMSM with coreless stator and double external rotor.